Women Liberty through Colonial Oppression: A Short Study on M. K. Gandhi and R. S. Hossain - Md. Eftekhairul (International Journal of Education, Teaching, and Social Sciences, 2023)
The point of the current paper is to reveal insight into women's condition within Indian Subcontinent during the colonial period. The investigation will fixate on the gendered place that women had to take, and on the male developed generalizations to which they were oppressed from an Enlightenment Feminist viewpoint. Begum Rokeya brought the social condition of women into mindfulness how a lady was obliged to comply with social built biases which made of her an item; all chances for education, prospect, freedom and improvement were shut to her. When the people of colonial India could feel the independence, they could realize the essence of women education. Colonialism not only depress men but also became the key factor to trap the women into a case-house. The permission of women’s education did not come automatically, but with a long struggle and well leading campaign. Only for Hindus, Mahatma Gandhi played an imperative part to support the dignity of women folk by stating that women were neither mere figures in the hands of male nor their opponents. Begum Rokeya Sakhawat Hossain, for both Muslims and Hindus, shouted the women's consciousness and women's freedom through education could play a vital issue to strengthen the man's heart for colonial freedom. They, both, wanted women's empowerment and equality in society; at the workstation; at the community, and even at family for sustainable-development of a nation. Their activism inspired modern women gliding to economic, political and mental growth. Nowadays, women is involving in all sphere of national or international sectors in the Indian Subcontinent